2012
DOI: 10.1155/2012/439836
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Body Granuloma: A Diagnosis Not to Forget

Abstract: Penetrating wounds of the foot are not uncommon. Many are caused by thorns or by fragments of wood that are retained in the foot, creating a foreign-body granuloma. The differential diagnosis for bony reaction to an unrecognised organic foreign body includes osteoid osteoma, chronic and acute osteomyelitis, tuberculosis granuloma, bone cyst, aneurysmal bone cyst, cortical fibrous defect, and neoplasm. We report the case of a boy suffering from a thorn inducing a lytic lesion of the fifth metatarsal that demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…This is true more so for a pediatric case, thereby increasing the risk of complications. [ 9 , 10 ] In the present case, the symptoms of the boy were edema and haphalgesia in the scrotum without any skin lesion such as needle entry hole. According to his medical history and positive physical signs, we initially diagnosed him with testicular torsion.…”
Section: Discussionmentioning
confidence: 61%
“…This is true more so for a pediatric case, thereby increasing the risk of complications. [ 9 , 10 ] In the present case, the symptoms of the boy were edema and haphalgesia in the scrotum without any skin lesion such as needle entry hole. According to his medical history and positive physical signs, we initially diagnosed him with testicular torsion.…”
Section: Discussionmentioning
confidence: 61%
“…Bone granulomas caused by foreign bodies in children are rare, with only a few cases described in the literature [3][4][5]. It was suggested that BGs originate from extension of the granulomatous tissue of the contiguous soft tissues [6].…”
Section: Discussionmentioning
confidence: 99%
“…Foreign body granulomas in soft tissues are well-known entities, both in adults and children [1][2]. On the other side, bone granulomas (BGs) originating from foreign bodies are a rare condition, especially in children, with very few cases reported in literature [3][4][5]. BGs may either originate from an inflammatory reaction to intraosseous foreign bodies or from contiguity to a soft tissues foreign body granuloma.…”
Section: Introductionmentioning
confidence: 99%
“…Organic material, particularly thorns, can cause an inflammatory tissue reaction, ranging from a localized foreign body granuloma to a severe soft tissue reaction including a significant synovitis with a painful joint and an osseous lesion with a lytic reaction or exceptionally an osteoblastic reaction as in our case or a combination of both [5] . The differential diagnosis for an osseous pathologic reaction to an unrecognized organic foreign body includes acute and chronic osteomyelitis, osteoid osteoma, tuberculosis granuloma, cortical fibrous defect, aneurysmal bone cyst, bone cyst, and neoplasm [6] .…”
Section: Discussionmentioning
confidence: 99%